ANALISIS PERENCANAAN PAJAK (TAX PLANNING) DALAM UPAYA MENINGKATKAN EFISIENSI BEBAN PAJAK PENGHASILAN BADAN PADA PT AKASHA WIRA INTERNASIONAL TBK - Herlisnawati, Dessy; Ahmad, Yola Fahmi (Universitas Pakuan, 2013)
Competition increases, the company is expected to make savings in all areas. One of the savings that can be done by the company is in the field of taxation, namely to streamline the burden of corporate income tax with tax planning. The purpose of this study was to investigate the implementation and effect of how the Tax Planning (Tax Planning) in Efforts to Increase the Efficiency of Corporate Income Tax Expense PT Akasha Wira International Tbk. The result showed that Tax Planning conducted by PT Akasha Wira International Tbk has not been implemented properly, this can be seen from the persistence of the cost of tax-expenditures that can still be maximized. Tax planning can still be maximized is considering providing tax benefits are included in the payroll, this planning can save the tax burden of 4.5%. So that the tax burden can be saved then the company should consider providing tax benefits to employees who entered into the payroll, thus increasing the operational costs of salaries, by itself will reduce tax payable.Keyword : Tax Planning, Equity, Income Tax, Efficiency.